Kajian Arah Tegasan dan Nilai RQD Berdasarkan Analisis Statistik Data Struktur Kekar - Dewi Rahmawaty Isa; Aang Panji Permana; Ronal Hutagalung (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2022)
The research location is in Gorontalo City. The location is an area that has geological structural conditions of high complexity. The study used statistical analysis of the robustness data to determine the direction of the firmness and the RQD (rock quality designation) value. The research objectives consist of two, namely knowing the direction of the stress (the main force of tectonic formation) and knowing the RQD value based on the analysis of joint data. To achieve these two objectives, it is carried out with a research method in the form of an inductive method. This method combines the results of a literature review, previous research and field data, all of which are comprehensively studied, analyzed, and synthesized. Statistical analysis (fan diagram) on joint data on granite rocks in Gorontalo City. The results and discussion resulted in the direction of maximum stress (Ï„1) = N 15oE and the direction of minimum stress (Ï„3) = N 75oW. The rock RQD value is 40.60% so that the rock quality in this research area is classified as moderate. The results of the measurement of the joint spacing at this station are obtained from a distance of (5-10) cm, so it is included in the weak scale so that the joint space strongly supports the occurrence of landslides.